Journal of Gastroenterology - Ueno, Yoshiyuki; Seno, Hiroshi; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
The Journal of Gastroenterology, which is the official publication of the Japanese Society of Gastroenterology, publishes Original Articles (Alimentary Tract/Liver, Pancreas, and Biliary Tract), Review Articles, Letters to the Editors and other articles on all aspects of the field of gastroenterology. Significant contributions relating to basic research, theory, and practice are welcomed. These publications are designed to disseminate knowledge in this field to a worldwide audience, and accordingly, its editorial board has an international membership.
Keywords: Gastroenterology; Hepatology; Abdominal surgery; Rectum -- Surgery; Surgical oncology; Gastroenterology; Hepatology; Abdominal Surgery; Colorectal Surgery; Surgical Oncology